Chronicles of refrigeration and air-conditioning in tropical Philippines : the cold facts (Manila, Philippines : De La Salle Universiry Press, 2015)
The purpose of this book is to inform the public of the importance of refrigeration in our lives . It was once in the past that ice is one of the priced commodities that spearheaded the development of Manila to the extent that power generation was mainly intended for ice production .
Part I. Before 1930s: No ice age and ice age -- Part II. 1930 to 1960s: Building and rebuilding the nation -- Part III. 1960 to 1990s: Boom, decline and recovery -- Part IV. 1990s and beyond: Toward a green-er Philippines .
Includes bibliographical references.
Keywords: AIR CCONDITIONING--CLIMATIC FACTORS